1/3(x-4)=5x-4(x-1)+22/3

Simple and best practice solution for 1/3(x-4)=5x-4(x-1)+22/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3(x-4)=5x-4(x-1)+22/3 equation:


1/3(x-4)=5x-4(x-1)+22/3

We simplify the equation to the form, which is simple to understand
1/3(x-4)=5x-4(x-1)+22/3

Simplifying:
+ 0.333333333333*(x-4)=5x-4*(x-1)+22/3

Simplifying:
+ 0.333333333333*(x-4)=5x-4*(x-1)+7.33333333333

Reorder the terms in parentheses
+( + 0.333333333333x-1.33333333333)=5x-4*(x-1)+7.33333333333

Remove unnecessary parentheses
+ 0.333333333333x-1.33333333333=+5x-4+*(+x-1+)+7.33333333333

Reorder the terms in parentheses
+ 0.333333333333x-1.33333333333=5x+(-4x+4)+7.33333333333

Remove unnecessary parentheses
+ 0.333333333333x-1.33333333333=+5x-4x+4+7.33333333333

We move all terms containing x to the left and all other terms to the right.
+ 0.333333333333x-5x+4x=+4+7.33333333333+1.33333333333

We simplify left and right side of the equation.
-0.666666666667x=+12.6666666667

We divide both sides of the equation by -0.666666666667 to get x.
x=-19

See similar equations:

| 2(x-2)+3=2x+6 | | 2x+7+x=7 | | 22-3x=1 | | 0.5(10x+8)=3x-6 | | x^2(x+4)+2x(x+4)-15(x+4)= | | 11x-8x+19-2=5 | | 1/6(x+2)=2x-3(4-x)-7 | | 4d-7d+18=3 | | 8=8m+14-9m | | -3=w+3 | | 5(4x+2x)-(8x-12)=68 | | 4a+8b-16c= | | 96wx^3y^3z^2-144w^3xy^2z^3= | | -8y+-2x+3x+4y+2=3 | | 10x-9(x+6)=31 | | -3x+7+4x=2 | | 14x-28=56 | | 7-0.0625x=-2 | | -4x-8=3(-x-4) | | 14n-4n=56+64 | | 3x+4y+2=2x+8y+3 | | -0.2q-4=9 | | 9a^3b^2-36a^3b-54a^2b^2= | | -6(10-2x)=24 | | 3X^2-3+8X=0 | | -14=b-15 | | 10b-4+3B+2= | | 14+5y=8y-10 | | 12-36=12x | | 4x+2x+13=55 | | 96=-16t+80t | | 12x-24=12x+24 |

Equations solver categories